Effect of Cataract Surgery (Phaco and Manual Small Incision Cataract Surgery) on the Corneal Endothelium (Medical Forum Monthly, 2021)
Objective: This study will investigate the relationship between phacoemulsification (active removal of cataracts) and manual tiny incision (passive removal of cataracts) on the corneal endothelial cell count.Study Design: Prospective Comparative studyPlace and Duration of Study: This study was conducted at the Department of Ophthalmology, Chandka Medical College & Shaheed Mohtarma Benazir Bhutto Medical University Larkana, from 1st August 2020 to 30th April 2021.Materials and Methods: The researchers investigated the effect of phacoemulsification, SICS, and cataract surgery on 100 patients who underwent this procedure using manual small incision cataract surgery (SICS). In order to investigate the correlation between nuclear cataracts and senile cortical cataracts, participants age 30 to 70 years were enrolled. Approximately 70% of the surgeries done by a single surgeon were collected for the study. The data were analyzed in SPSS version 21.0Results: Phacoemulsification was utilised on a total of 100 patients. In the case of the SICS method, 50 patients received phacoemulsification and 50 patients did not. Lower endothelial count loss was detected with manual SICS, with 22 eyes showing a count lossiofibetweeni100-500icells, and an increase of over 1500 cells was found in 8 eyes (4 eyes). was shown to be at 18% of endothelial cell loss with fewer than 100 endothelial cells lost (9 eyes). When looking at the data in phacoemulsification, it was revealed that theiendothelialicellicountilossiofiunderi100icellsiwas highest at 46% (23 eyes), and greater than 1500 cells was undetected in this study.Conclusion: In this study, endothelial cell count loss after phacoemulsification surgery was found to be smaller than SICS. After phacoemulsification surgery was found to be super or to manual SICS because it prevented the endothelial cells from receiving extensive injury, which helped to ensure that patients immediately post-surgery would have a good BCVA, as opposed to a lesser-than-desired BCVA experienced by patients who received manual SICS.